Assessing the Sehat Card Plus programme database: An in-depth analysis of patient demographics, healthcare utilization, and financial expenditure in Khyber Pakhtunkhwa, Pakistan - Junaid Ur Rehman Siddiqui; Waqas Hameed; Shifa Salman Habib; Kiran Sohail Azeemi; Ali Hussaini; Asma Altaf Hussain Merchant; Adil Haider; Sameen Siddiqi (Journal of the Pakistan Medical Association, 2024)
Objective: This study utilizes the Sehat Card Plus (SCP) programme's health insurance database in Khyber Pakhtunkhwa (KP) to assess demographic characteristics, healthcare utilization patterns, and disease profiles of beneficiaries. Additionally, it analyses processes related to claims, settlements with hospitals, and the financial expenditure of the programme. Methods: The study employed the programme's third-party managed Management Information System (MIS) to obtain a sample of 100,029 beneficiary records from January 1st, 2021, to October 31st, 2022, across 10 designated study districts in KP province. After removing 5,642 duplicate records, the final dataset comprised 94,387 unique beneficiary records, subjected to descriptive statistical analysis. Results: Among women, 25,745 (50%) of admissions were in the 15-45 years age group, while 14,189 (33%) of male admissions were in the 60 and above age group. The hospital mortality rate was 5,200 (5.5%), with an average cost per admission of PKR 31,395. KP government spent PKR 2.96 billion on 94,387 patients, allocating PKR 828 million to treat cardiovascular diseases. The average cost of treating ischaemic heart disease was PKR 89,919. Empanelled hospitals took an average of 51±52.8 days to send claims, and SLIC took 21±26.1 days to settle claims. Conclusion: The third party administrators of the SCP programme maintain a robust database, capturing all hospital admissions under the SCP programme. However, improvements in database quality and the incorporation of new indicators are recommended for enhanced and independent programme monitoring and evaluation, especially with regard to equity. Keywords: Health Insurance Database, Healthcare Utilization, Health Insurance Program Evaluation